Mold-making technology at architectural compound 60 (CA-60): A newly discovered ceramic workshop at Huacas de Moche, Peru - Mosna, F.; Rengifo, C. (Academic Press, 2025)
Ceramic molding is often addressed as a simple, repetitive, and standardized technique. Similarly, mold-making, though much less studied than molding itself, is frequently viewed as equally straightforward. Yet what specific gestures, techniques, and tools are involved in mold-making? Does internal technical variability exist behind apparent external standardization? What insights into ancient craft production can mold-making evidence provide? This paper addresses these questions through a technological study of molds from a recently discovered ceramic workshop at Huacas de Moche (Trujillo, Peru). Our study reveals that mold-making comprises multiple complex sequential steps with significant technological variation. We suggest that local Moche artisans maintained autonomy in their mold production methods, employing diverse technological approaches while sharing a common artistic repertoire, meanwhile elite oversight ensured quality standards in final products.
Keywords: Molding technology; Standardization; Mass production; https://purl.org/pe-repo/ocde/ford#2.11.03